2022
DOI: 10.3390/medicina59010055
|View full text |Cite
|
Sign up to set email alerts
|

A Chinese Classical Prescription Chaihu Shugan Powder in Treatment of Post-Stroke Depression: An Overview

Abstract: Post-stroke depression (PSD) is the most common mental health problem after a stroke with an incidence of up to 33%. PSD has a negative impact on the rehabilitation and recovery of motor and cognitive dysfunction after a stroke and significantly increases the chance of the recurrence of neurovascular events. At present, medication is the preferred method of coping with PSD. Modern medicine is still unclear regarding the pathogenesis of PSD, with clinical drug treatment mostly using antidepressants, such as sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…Sadeghi et al [ 63 ] reported that when comparing the two treatments' effects on patients with mild and moderate depression, they discovered that Hypericum perforatum was more effective than antidepressants. Hypericin and several flavonoids were identified as the primary antidepressant components in Jin Si Tao ( Hypericum monogynum L.), according to an analysis of clinical data by Gao et al [ 64 ]. These compounds may potentially participate in the treatment of depression by exerting inhibitory effects on 5-hydroxytryptamine, monoamine oxidase B, and monoamine oxidase A. Additionally, they control gene expression in the hypothalamus and the hypothalamic-adrenal axis.…”
Section: Overview Of Tcmmentioning
confidence: 99%
“…Sadeghi et al [ 63 ] reported that when comparing the two treatments' effects on patients with mild and moderate depression, they discovered that Hypericum perforatum was more effective than antidepressants. Hypericin and several flavonoids were identified as the primary antidepressant components in Jin Si Tao ( Hypericum monogynum L.), according to an analysis of clinical data by Gao et al [ 64 ]. These compounds may potentially participate in the treatment of depression by exerting inhibitory effects on 5-hydroxytryptamine, monoamine oxidase B, and monoamine oxidase A. Additionally, they control gene expression in the hypothalamus and the hypothalamic-adrenal axis.…”
Section: Overview Of Tcmmentioning
confidence: 99%